Neoadjuvant ipilimumab plus nivolumab therapy as a potential organ preservation strategy in mucosal melanoma: case report - Ong, Claire V.; Samlowski, Wolfram (Frontiers in Oncology, 2024)
Mucosal melanoma represents an uncommon melanoma subtype. Wide excision has long represented the standard therapeutic approach. Unfortunately, there is a high relapse rate and mortality. Neoadjuvant therapy with ipilimumab plus nivolumab has shown significant activity in cutaneous melanoma. We present two cases of mucosal melanoma, each with potential regional dissemination, who were treated with neoadjuvant immunotherapy with minimal toxicity. Both patients were closely monitored and achieved radiologic and pathologic complete responses. These patients were able to avoid radical surgery and related functional consequences. Both patients remain recurrence-free with protracted follow-up. The potential usefulness of neoadjuvant immunotherapy as an organ preservation strategy in mucosal melanoma deserves further evaluation in prospective clinical trials.